Tuberculosis progression rates in U.S. Immigrants following screening with interferon-gamma release assays - Robert J. Blount; Minh-Chi Tran; Charles K. Everett; Adithya Cattamanchi; John Z. Metcalfe; Denise Connor; Cecily R. Miller; Jennifer Grinsdale; Julie Higashi; Payam Nahid (BMC, 2016)
Abstract Background Interferon-gamma release assays may be used as an alternative to the tuberculin skin test for detection of M. tuberculosis infection. However, the risk of active tuberculosis disease following screening using interferon-gamma release assays in immigrants is not well defined. To address these uncertainties, we determined the incidence rates of active tuberculosis disease in a cohort of high-risk immigrants with Class B TB screened with interferon-gamma release assays (IGRAs) upon arrival in the United States. Methods Using a retrospective cohort design, we enrolled recent U.S. immigrants with Class B TB who were screened with an IGRA (QuantiFERON ® Gold or Gold In-Tube Assay) at the San Francisco Department of Public Health Tuberculosis Control Clinic from January 2005 through December 2010. We reviewed records from the Tuberculosis Control Patient Management Database and from the California Department of Public Health Tuberculosis Case Registry to determine incident cases of active tuberculosis disease through February 2015. Results Of 1233 eligible immigrants with IGRA screening at baseline, 81 (6.6 %) were diagnosed with active tuberculosis disease as a result of their initial evaluation. Of the remaining 1152 participants without active tuberculosis disease at baseline, 513 tested IGRA-positive and 639 tested IGRA-negative. Seven participants developed incident active tuberculosis disease over 7730 person-years of follow-up, for an incidence rate of 91 per 100,000 person-years (95 % CI 43-190). Five IGRA-positive and two IGRA-negative participants developed active tuberculosis disease (incidence rates 139 per 100,000 person-years (95 % CI 58-335) and 48 per 100,000 person-years (95 % CI 12-193), respectively) for an unadjusted incidence rate ratio of 2.9 (95 % CI 0.5-30, p = 0.21). IGRA test results had a negative predictive value of 99.7 % but a positive predictive value of only 0.97 %. Conclusions Among high-risk immigrants without active tuberculosis disease at the time of entry into the United States, risk of progression to active tuberculosis disease was higher in IGRA-positive participants compared with IGRA-negative participants. However, these findings did not reach statistical significance, and a positive IGRA at enrollment had a poor predictive value for progressing to active tuberculosis disease. Additional research is needed to identify biomarkers and develop clinical algorithms that can better predict progression to active tuberculosis disease among U.S. immigrants.